PENGARUH PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SEKOLAH DASAR KELAS V - Agustian, Egi; Sujana, Atep; Kurniadi, Yedi (Universitas Pendidikan Indonesia, 2015)
This research is experimental research in the research design is pretest-posttest control group design to find out the influence of open-ended approach on creative-mathematic thinking skill of student's grade V SD. The population of this research is all student's grade V of SD considering middle-group category based on the average score on a mathematics national exam at SD/MI level in the entire Rancakalong region. Meanwhile, the samples of this research are SDN Pasirbenteng II as experimental group and SDN Pasirbiru as a control group. The instruments in this research consist of test, affective scale, observation format of teachers’ performance, observation format of students’ activities and interview. The result from this research proves that learning using the open-ended approach can significantly increase a creative mathematic thinking of student's grade V SD. It can be seen from the findings of data analysis. Based on the research, students’ response to mathematics learning using open-ended tends to show a positive response that means students have good tendency of interest and enthusiasm to the learning. Thus, it can be concluded that open-ended is one of the solutions to increase creative - mathematic thinking skill of student's grade V SD. Keywords: open-ended approach, creative-mathematic thinking skill.